2013
DOI: 10.1093/mnras/stt2108
|View full text |Cite
|
Sign up to set email alerts
|

Early evolution of clumps formed via gravitational instability in protoplanetary discs: precursors of Hot Jupiters?

Abstract: Although it is fairly established that Gravitational Instability (GI) should occur in the early phases of the evolution of a protoplanetary disk, the fate of the clumps resulting from disk fragmentation and their role in planet formation is still unclear.In the present study we investigate semi-analytically their evolution following the contraction of a synthetic population of clumps with varied initial structure and orbits coupled with the surrounding disk and the central star. Our model is based on recently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 52 publications
1
43
1
Order By: Relevance
“…While the clump has a mass at the high end of the mass distribution of extrasolar gas giants, we note that the gas accretion rate of ∼10 −7 M e yr −1 implies that the protoplanet will gather only 5 Jupiter masses, hence its mass would less than double, in 5 × 10 4 years. The latter timescale is more than an order of magnitude longer than the characteristic timescale of migration and consequent tidal mass loss found for massive planets in gravitationally unstable disks (Malik et al 2015), suggesting that the mass of the clump should remain in the gas giant regime, if not decrease (see Galvagni & Mayer 2014). Furthermore, higher resolution simulations capable of following the collapse of clumps to near-planetary densities, have determined that, irrespective of migration, the planetary mass resulting at the end of the collapse is at least a factor of two lower since a significant fraction of the mass resides in an extended, loosely bound circumplanetary disk, which would be stripped by stellar tides even at relatively large distances from the central star (Galvagni et al 2012;Galvagni & Mayer 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the clump has a mass at the high end of the mass distribution of extrasolar gas giants, we note that the gas accretion rate of ∼10 −7 M e yr −1 implies that the protoplanet will gather only 5 Jupiter masses, hence its mass would less than double, in 5 × 10 4 years. The latter timescale is more than an order of magnitude longer than the characteristic timescale of migration and consequent tidal mass loss found for massive planets in gravitationally unstable disks (Malik et al 2015), suggesting that the mass of the clump should remain in the gas giant regime, if not decrease (see Galvagni & Mayer 2014). Furthermore, higher resolution simulations capable of following the collapse of clumps to near-planetary densities, have determined that, irrespective of migration, the planetary mass resulting at the end of the collapse is at least a factor of two lower since a significant fraction of the mass resides in an extended, loosely bound circumplanetary disk, which would be stripped by stellar tides even at relatively large distances from the central star (Galvagni et al 2012;Galvagni & Mayer 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Whether disk fragmentation is a common outcome of GI and results in long-lived objects that contract to become gas giant planets (Mayer et al 2004;Boss 2005), or even lower mass planets via tidal mass loss Galvagni & Mayer 2014), is still debated (Helled et al 2014). However, disk instability offers a natural explanation for the massive planets on wide orbits discovered via imaging surveys in the last decade (e.g., Marois et al 2008) because the conditions required for disk fragmentation, namely a Toomre instability parameter Q < 1.4 and short radiative cooling timescales, should be satisfied in the disk at R > 30 au Rafikov 2007;Clarke 2009;Meru & Bate 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike most of the GI models [e.g. 55,257], GI/TD model of Nayakshin [63] can also explain the formation of low-mass planets. The model of Nayakshin [63], as the CA models, also predicts high occurrence rate of these planets at low metallicities.…”
Section: Low-mass Planets and Metallicitymentioning
confidence: 99%
“…Forgan & Rice (2013) find that TD is incapable of producing any planets at small separations (R < ∼ 10 AU) since most of their gas fragments are tidally disrupted before massive solid cores could form within them. Galvagni & Mayer (2014) did not include grain sedimentation in their models, hence could not say anything about the post-disruption core-dominated planets. However, their study found a wealth of Jovian mass planets that successfully migrated into the inner disc, avoiding tidal disruptions, and hence they suggested that TD may well be effective in producing a hot-Jupiter like population of gas giants.…”
Section: Introductionmentioning
confidence: 99%